Genital psoriasis: A prospective, observational, single-centre study on prevalence, clinical features, risk factors, and its impact on quality of life and sexual health - Yi, Ooi; Huan, Khor; Har, Loo; Ali, Norazlima; Chiang, Tan (Indian journal of dermatology, 2022)
Background: Genital psoriasis is often under-recognized and the exact burden is unknown in Malaysia. Objectives: To identify the prevalence of genital psoriasis, its clinical features, risk factors, and impact on quality of life and sexual health. Methods: This prospective, observational study was conducted in the dermatology clinic of our hospital from 1st September 2020 until 31st March 2021, involving all adult patients with psoriasis. The genital examination was performed and the subjects were interviewed using questionnaires. Results: A total of 262 patients were recruited, with a male to female ratio of 1.5:1 (mean age of 51 years old). They comprised 42.0% Chinese, followed by 36.6% of Malay, 21.4% of Indians and others. Up to 46.1% of patients had a current or history of genital psoriasis. The most common area involved for males was the scrotum (44.1%) and labia majora (62.5%) for female patients. Itching (79.2%) was the most frequent symptom encountered. Chinese patients had 2.67 times odd (CI 1.55-4.61) of having genital psoriasis compared to non-Chinese patients. Other independent risk factors included flexural involvement, male gender, and Type 1 psoriasis. Genital psoriasis was associated with greater impairment on quality of life and sexual health (mean total Dermatology Life Quality Index: 8.8 vs 6.5, P = 0.006), International Index of Erectile Function (mean: 48.5 vs 57.0, P = 0.011) and revised version of Female Sexual Distress Scales (mean: 20.7 vs 11.4, P = 0.022). Conclusions: Genital psoriasis is common and it has a profound impact on patients.